Keterkaitan antara Turbiditas Serum dan Laju Endap Darah dengan Kerusakan Hati pada Sapi Bali - Harjono Utama, Iwan; Yanse Rumlaklak, Yanne; Ayu Dwita Karmi, Dewa; Sagung Kendran, Anak Agung; Kayati Widyastuti, Sri; Berata, I Ketut; Eka Setiasih, Luh (Jurnal Veteriner; Vol 11 No 3 (2010))
This research was aimed to observe serum turbidity and blood sedimentation rate (ESR) as a predictorof hepatic damage in bali cattle. Two hundred whole blood and sera from 80 male and 120 female bullswere sampled from Mambal abbatoir, Badung, Bali. All blood were examined for their ESR and sera werefor their turbidity using ZnSO4 solution, besides we observed some hepatic damages pathology anatomicallywithout incision such as : internal bleeding, formation of connective tissue, swelling, and bile-ductenlargement. all of those damages were scaled graded from 0 (without abnormality) to 4 (more than 75%liver surface has abnormalities). Results showed all 86% bulls (male 32% and female 54%) have their seraturbidity ranged from 1,01-2,00, besides, 89% bulls (45% male and 44% female) have their ESR rangedfrom 3-8 mm in 24 hours. Most of liver abnormalities were : swelling (58%), bile-duct enlargement (50,5%),connective tissue formation (73%), and bleeding (59%) most of them were falling in scale 1 (less than 25%of liver surface area). Also, ESR has positive correlation (P<0,05) with connective tissue formation andserum turbidity value could be used to predict internal bleeding and connective tissue formation. It couldbe concluded ESR value could be used as a predictor of connective tissue formation and serum turbidityvalue could be used as a predictor for internal bleeding and connective tissue formation in bali cattle.
Keywords: erythrocyte sedimentation rate, serum turbidity, liver abnormalities, bali cattle